Public Attitude in Yugyakarta Towards Television Advertising - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
This study was conducted to learn public attitude to television advertising, especially public attitude towards television advertisements aired during commercial breaks. The results showed that public attitude towards television advertising are somewhat favorable. Apparently, male viewers tend to pay more attention to television advertisements than female. Additionally, compared to nonstudents, students find TV advertisements more irritating.